The influence of word wall on students interest and learning outcomes at seventh grade SMPIT Darul Qur-an Mulia Bogor - Alkoni Mahesa; Muhammad Sofian Hadi; Korneilis Korneilis (English Language in Focus (ELIF), 2023)
This study focuses on investigating the impact of word walls on students' interest and learning outcomes in the seventh grade at SMPIT Darul Qur-an Mulia Bogor. The research adopts a quantitative research method employing a pretest-posttest control group design. The population for this study comprises seventh-grade students at SMPIT Darul Qur-an Mulia Bogor, with a sample selected using a simple random sampling technique. The experimental group receives the intervention of the word wall strategy, while the control group does not receive any form of treatment or intervention. A pretest is conducted to assess the students' initial vocabulary comprehension. The Word Wall strategy is implemented in two cycles, each comprising three meetings and a post-test. The findings reveal that the Word Wall strategy positively influences students' interest and learning outcomes, as evidenced by improved scores, increased success rates, and enhanced vocabulary mastery. The implementation of word walls creates an engaging learning environment that enhances students' interest and motivation, leading to improved academic performance.